INTEGRATED STRATEGIC MANAGEMENT FRAMEWORK: EVIDENCE FROM PT GOTO GOJEK TOKOPEDIA TBK - Surya Soebroto; Joseph Susanto (Jurnal Media Ekonomi (JURMEK), 2026)
Abstract Purpose: This study analyzes the strategic position of PT GoTo Gojek Tokopedia Tbk. using an integrated strategic management framework to formulate strategies that enhance its competitiveness in Indonesia's digital platform industry. Research Methodology: An integrated framework comprising PESTEL Analysis, Porter's Five Forces, the EFE Matrix, IFE Matrix, Competitive Profile Matrix (CPM), SWOT Matrix, IE Matrix, SPACE Matrix, BCG Matrix, and Grand Strategy Matrix was applied using secondary data from annual reports, industry reports, and other credible sources. Results: The findings indicate that Indonesia's digital economy offers significant growth opportunities despite intense competition, regulatory changes, and cybersecurity challenges. The EFE and IFE matrices show that GoTo has moderate strategic capabilities, while the CPM identifies Shopee as its strongest competitor. The IE Matrix positions GoTo in the Hold and Maintain quadrant, the SPACE Matrix indicates a Competitive position, the BCG Matrix classifies its e-commerce business as a Star, and the Grand Strategy Matrix places the company in Quadrant I. Overall, the integrated analysis consistently recommends market penetration and product development as the most appropriate strategies. Conclusions: GoTo's integrated digital ecosystem provides a strong competitive foundation, and the integrated framework offers a comprehensive basis for strategic decision-making. Limitations: This study relies exclusively on secondary data, and the weighting and rating of strategic factors involve researcher judgment, which may introduce subjectivity into the analysis. Contributions: This study contributes to the strategic management literature by demonstrating that integrating multiple strategic analysis frameworks into a unified strategy formulation process generates more comprehensive and consistent strategic recommendations than applying individual analytical tools separately. The findings also extend the applicability of the strategic management framework of David and David (2023) to digital platform companies operating in highly dynamic and competitive environments.